2011
DOI: 10.1002/ange.201007987
|View full text |Cite
|
Sign up to set email alerts
|

Wasserspaltung mit Cobalt

Abstract: Die Energieversorgung der Zukunft kann nur durch grundlegende Neuerungen auf dem Gebiet billiger, nachhaltiger und effizienter Systeme zur Gewinnung und Speicherung von Energie aus erneuerbaren Quellen oder aus Sonnenlicht gesichert werden. Die Erzeugung von Wasserstoff, einem Brennstoff mit bemerkenswerten Eigenschaften, durch die Wasserspaltung mithilfe von Sonnenlicht ist in diesem Zusammenhang ein vielversprechender Ansatz. Während die aktiven Zentren von wasserspaltenden Enzymen – wie Hydrogenasen und Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(58 citation statements)
references
References 232 publications
0
52
0
6
Order By: Relevance
“…Redox properties were evaluated for three diiron hydrides of differing basicities, redox potentials, and steric bulk ( Figure 1). The cyclic voltammograms of [HFe 2 (pdt)(CO) 4 Figure 1, the redox event becomes more reversible for the more demanding reductions, as reflected by changes in i pc /i pa from 0.52 to 0.99. These results suggested that [H1] 0 should be sufficiently stable to allow isolation.…”
Section: ■ Resultsmentioning
confidence: 97%
“…Redox properties were evaluated for three diiron hydrides of differing basicities, redox potentials, and steric bulk ( Figure 1). The cyclic voltammograms of [HFe 2 (pdt)(CO) 4 Figure 1, the redox event becomes more reversible for the more demanding reductions, as reflected by changes in i pc /i pa from 0.52 to 0.99. These results suggested that [H1] 0 should be sufficiently stable to allow isolation.…”
Section: ■ Resultsmentioning
confidence: 97%
“…[7,8] Mononuclear cobaltand nickel-based compounds, which have long been known as H 2 -production catalysts, [9][10][11] have been recently revisited. [12][13][14][15][16] Examples of mononuclear [17] and binuclear [18] molybdenum-based catalysts have also been reported. Iron is the most abundant transition metal.…”
Section: Introductionmentioning
confidence: 95%
“…19,20 These reported systems, containing light absorbers (QDs), external cocatalysts and source of electrons, have shown remarkable activity and stability with turnover number (TON) much higher than those of organic dyes 35 and metal complexes contained systems. [21][22][23] Unfortunately, all of the current systems are performed well only in the presence of large amounts of chemical sacrificial electron donors. To avoid the use of any sacrificial agent and generate H 2 in an environmentally friendly manner, photoelectrochemical (PEC) 40 production of H 2 is an ideally clean and renewable mean that integrates solar energy collection and water reduction into a single photoelectrode.…”
mentioning
confidence: 99%